1. 4x - 8 = - 32 + 2x
Ok, first of all we need to collect "like-terms", that is, move all the x's to one side and the numbers to the other.
So we get: 4x - 2x = -32 + 8
This means that 2x = -24, then divide both sides by 2, we get:
x = -12
2. - 3(1x + 3) = - 33
Divide both sides by -3, we get (1x + 3) = 11
1x = 11 - 3, which is the same as x = 8
3. Solve: 3x + y = 5 and -3x - 2y = -1
Ok, these are what we call simultaneous equations and the method I'll be using is one of the methods know as substitution, first of all, from 3x + y = 5, we can see that y = 5 - 3x, this means whenever we see y in the second equation we can replace with 5 - 3x, so -3x - 2(5 - 3x) = -1.
Expandinf your brackets, -3x - 10 + 6x = -1, and then collect like terms as before: 3x = 9, giving x = 3